2018
DOI: 10.3748/wjg.v24.i6.706
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expressed vasoactive intestinal peptide analogue ameliorates TNBS-induced colitis in rats

Abstract: AIMTo investigate the modulatory effect of recombinant-expressed vasoactive intestinal peptide (VIP) analogue (rVIPa) on trinitrobenzene sulfonic acid (TNBS)-induced colitis in rats.METHODSForty-eight rats were randomized into six groups: normal control group (Control), model control group (TNBS), ethanol treatment group (ETOH), and VIP treatment groups with different dosage (rVIPa1nmol, rVIPa2nmol, rVIPa4nmol). Diarrhea and bloody stool were observed. Colonic damage was evaluated histologically. The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Since VIP shows neuroprotective properties [ 15 , 16 , 17 , 18 , 19 , 20 ], controls the immune reactions [ 41 ] and plays a key role during inflammatory processes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], the possibility of the use of VIP analogs as drugs during intestinal inflammations has been tested in recent years. The results showed that VIP analogs ameliorated changes in the colon after experimentally induced colitis in rats and reduced necrosis, hyperemia and swelling [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since VIP shows neuroprotective properties [ 15 , 16 , 17 , 18 , 19 , 20 ], controls the immune reactions [ 41 ] and plays a key role during inflammatory processes [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], the possibility of the use of VIP analogs as drugs during intestinal inflammations has been tested in recent years. The results showed that VIP analogs ameliorated changes in the colon after experimentally induced colitis in rats and reduced necrosis, hyperemia and swelling [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability in mice was detected, the datas suggested that serum glucan binding levels in the rottlerin team were below those in the only DSS-treated mice, but similar to the WT mice (Figure 2E). Bacteria extracted from mln 10 and liver tissue are cultured by aseptic technology. In the rottlerin group, the probability of bacterial transfer to liver and MLN was below the DSS-treated group, but similar to the WT mice (Figure 2F-G).…”
Section: Rottlerin Treatment Improved the Distribution Of Tj Proteinsmentioning
confidence: 99%
“…Several bacterial pathogens can alter TJs by altering the distribution of occludin and ZO-1. The abnormal expression of TJ proteins in the epithelial cell monolayer may disrupt the structure and function of TJs, thereby destroying the completeness of barrier [10] . Inflammation is considered to be the basic mechanism of the pathophysiology of intestinal damage [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Dietary and microbiota changes can protect the intestinal barrier function, which is the case for glutamine (Li et al, 1994), bacteria-derived lactic acid (Ren et al, 2018) and butyrate (Kelly et al, 2015). Other interventions disrupt the gut barrier, as in the case of DSS (Poritz et al, 2007), TNBS (Bregeon et al, 2016; Xu et al, 2018) or heavy metal supplementation (Zhai et al, 2016), low protein (Eyzaguirre-Velasquez et al, 2017) or high fat diet (Hamilton et al, 2015), infection (Guttman et al, 2006; Goossens et al, 2018) or CLP (Parida et al, 2015). These models can be considered to have good construct validity for organic diseases (i.e., those where morphological and/or biochemical features are altered) where barrier function is compromised.…”
Section: Studying Gut Barrier Alterations In Animal Modelsmentioning
confidence: 99%
“…These models can be considered to have good construct validity for organic diseases (i.e., those where morphological and/or biochemical features are altered) where barrier function is compromised. For example, DSS or TNBS supplementation in rodents and IL-10 knockout mice are well known models of colitis (Shi et al, 2014; Li et al, 2018; Xu et al, 2018), which is achieved through different mechanisms: DSS induces epithelial injury with exposure of the lamina propria and submucosa to luminal antigens, resulting in inflammation which ultimately alters the gut barrier; TNBS acts as a hapten and also induces inflammation but through Th1-mediated immune responses, which has been shown both in murine (Low et al, 2013) and swine models (Bregeon et al, 2016). IL-10 knockout mice spontaneously develop bowel inflammation, which is associated to colon dysbiosis (Shi et al, 2014).…”
Section: Studying Gut Barrier Alterations In Animal Modelsmentioning
confidence: 99%